1998
DOI: 10.1111/j.1574-6968.1998.tb13304.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo apoptosis of hepatocytes in guinea pigs infected withLeptospira interrogansserovar icterohaemorrhagiae

Abstract: To investigate the contribution of the previously demonstrated in vitro apoptosis to the pathogenesis of leptospirosis, guinea pigs were infected with Leptospira interrogans serovar icterohaemorrhagiae strain Verdun and sequentially killed to collect target organs involved in the natural history of the disease (liver, kidneys, lungs, spleen and heart). The combination of histopathological procedures and a specific TUNEL assay showed a significant Leptospira-induced programmed cell death of hepatocytes with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 16 publications
(14 reference statements)
2
14
0
Order By: Relevance
“…Our finding that L. interrogans attaches better to cadherins than does the L. biflexa is consistent with previous data showing that pathogenic strains of Leptospira bind epithelial and endothelial cells more efficiently than saprophytic strains [2], [5], [6], [9], [11]. Several studies also demonstrated that L. biflexa adheres well to inert surfaces such as glass and plastic [8], [10], [67].…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that L. interrogans attaches better to cadherins than does the L. biflexa is consistent with previous data showing that pathogenic strains of Leptospira bind epithelial and endothelial cells more efficiently than saprophytic strains [2], [5], [6], [9], [11]. Several studies also demonstrated that L. biflexa adheres well to inert surfaces such as glass and plastic [8], [10], [67].…”
Section: Discussionsupporting
confidence: 92%
“…Using the virulent Leptospira interrogans Icterohaemorragiae strain Verdun [45],[46], we determined the dose of 10 8 live leptospires injected via the intra-peritoneal route as leading to ca. 50% mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Much interest has developed recently concerning the role of apoptosis in the pathogenesis of bacterial disease, although to date there have been no reports to demonstrate evasion of host cell apoptosis by bacterial organisms (28,29). Several bacterial agents have been shown to exert a proapoptotic influence on host cells (28,30,31), and it can only be speculated whether the capacity to induce host cell apoptosis evolved as a cellular host defense strategy or whether it provided the bacterial organism with a selective advantage. Members of the genus Rickettsia, are unique among bacterial organisms in that they are strict obligate intracellular parasites requiring a viable host cell for survival and replication.…”
Section: Discussionmentioning
confidence: 99%